Prevalence of positive TST among healthcare workers in high-burden TB setting in Peru - Juana Sedamano; Alvaro Schwalb; Rodrigo Cachay; Carlos Zamudio; César Ugarte-Gil; Gabriela Soto-Cabezas; César V. Munayco; Carlos Seas (BMC, 2020)
Abstract Background Tuberculosis (TB) transmission has long been recognized as an important occupational hazard for healthcare workers (HCWs). HCWs have a 5.8% annual risk of exposure and three times greater risk of developing active TB than the general population. Methods We conducted an observational cross-sectional study between September 2014 and March 2015 among HCWs in a high-burden TB setting in Lima to estimate the prevalence of positive Tuberculin Skin Test (TST) and to investigate factors associated with a positive TST. Results Two hundred forty participants were included in the analysis; TST was administered to 190 (79.2%) while the rest were exempt due to a previous positive TST result, history of TB, or test refusal. A positive TST result was found among 56.2% of participants to whom the TST was applied (95% CI: 49.22-63.55%). When considering those who had a previous positive TST result and those with a history of TB, the prevalence of a positive TST result was 64.3% (95% CI: 57.8-70.3%). No significant differences were observed between clinical/paramedical and administrative staff in the health center. The use of N95 masks during work hours was reported by 142 (69.9%) participants. Prevalence ratios (PR) show that workers with more than 120 months as a HCW were 1.44 times more likely to be TST positive. The multivariate analysis found that HCWs with over 10 years of service were 1.52 times more likely to be TST positive. Conclusion This study supports previous reports that TB infection is an occupational hazard for HCWs. Prevention of TB transmission through control measures, as well as timely diagnosis of LTBI in this particular high-risk group, is critical for individual and public health.